IMPROVING STUDENT'S CREATIVE THINKING ABILITY THROUGH APPLICATION OF JOYFULL LEARNING METHODS IN SD NEGERI I CISOMANG SCHOOL - Eneng Jubaedah; Rini Sriwahyuni; Hana Sakura Putu Agra (COLLASE (Creative of Learning Students Elementary Education), 2018)
Research was motivated by the lack of ability to think creatively of elementary school students in Cisomang State Elementary School I. In general, the long-term goal of this research program is to improve students' creative thinking skills through the application of joyful learning methods at Cisomang State Elementary School I. Specifically, the specific targets to be achieved are as follows: (1). Providing enjoyable learning to improve students' creative thinking skills; (2). Provide fun and meaningful ways of learning through joyful learning methods. This type of research is Classroom Action Research (CAR). The study design used the Kemmis and Mc Taggart models. The subject of the research was the fourth grade students of SD Negeri I Cisomang. Data collection techniques use interviews and documentation. Data analysis techniques using qualitative and quantitative descriptive. The results showed that the application of joyful learning methods could improve the creative thinking skills of IVB graders in science learning at Cisomang Elementary School I.Keywords: Joyfull Learning Method, Creative Thinking Ability.